Toner and two-component developer containing the same

The toner composition, featuring a blend of specific resins with tailored SP values and melting temperatures, addresses the issues of reduced durability and hot offset resistance in existing toners, achieving enhanced performance and longevity.

JP7662471B2Active Publication Date: 2025-04-15SHARP KK
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021152376
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-17
Publication Date
2025-04-15
Estimated Expiration
2041-09-17

AI Technical Summary

Technical Problem

Existing toners with compatible polyester resins exhibit reduced durability and hot offset resistance due to decreased viscosity at high temperatures, leading to seizure phenomena during long-term use.

Method used

A toner composition comprising a blend of amorphous resin A, amorphous resin B, hybrid resin C, and crystalline resin D, with specific SP values and melting temperatures, which maintains high viscosity at high temperatures and improves dispersion and durability.

Benefits of technology

The toner achieves excellent hot offset resistance and low-temperature fixing properties while minimizing the likelihood of seizure phenomena over extended periods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662471000001
    Figure 0007662471000001
  • Figure 0007662471000002
    Figure 0007662471000002
  • Figure 0007662471000003
    Figure 0007662471000003
Patent Text Reader

Abstract

To provide a toner which is less likely to cause a burning phenomenon over a long period of time and has excellent hot-offset resistance and low-temperature fixability, and a two-component developer containing the same.SOLUTION: A toner has toner particles containing a resin, a colorant and a release agent, wherein the resin contains an amorphous resin A containing polyester as a main component, an amorphous resin B containing polyester as a main component, an amorphous resin formed of a hybrid resin C having a polyester moiety and a vinyl copolymer moiety, and a crystalline resin D containing polyester as a main component, the amorphous resin A has an SP value of 10.85-11.20(cal / cm3)1 / 2 and a melting temperature Tm of 90-110°C, the amorphous resin B has an SP value of 10.85-11.20(cal / cm3)1 / 2 and a melting temperature Tm of 130-150°C, and the hybrid resin C has an SP value of 10.50-10.80(cal / cm3)1 / 2 and a melting temperature Tm of 125-145°C.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a toner and a two-component developer containing the toner. More specifically, the present invention relates to a toner that is unlikely to cause burn-in over a long period of time and has excellent hot offset resistance and low-temperature fixing properties, and a two-component developer containing the toner. [Background technology]

[0002] 2. Description of the Related Art In recent years, with the remarkable development of office automation equipment, electrophotographic apparatuses (image forming apparatuses) such as copying machines, printers, and facsimile machines that utilize electrophotographic technology have come into widespread use. Furthermore, the use of contact charging methods using rollers is becoming more common, and electrophotographic devices such as digital copiers and printers are becoming longer-lasting, more compact and faster. Toners used in these devices are being fixed at lower temperatures to save energy.

[0003] In order to improve the low-temperature fixing property of the toner, various techniques have been proposed. For example, Japanese Patent Laid-Open Publication No. 2017-116807 (Patent Document 1) proposes a toner that can be fixed at low temperatures, has high saturation and brightness, and is free of image defects such as white spots, and that has pulverized toner particles containing amorphous resin A and amorphous resin B having specific softening points Tm and solubility parameters SP values ​​and a specific relative relationship between them, resin composition (hybrid body) C in which an aliphatic hydrocarbon unit and a vinyl polymerization unit are chemically bonded, crystalline polyester resin D, wax, and a colorant. In order to improve the low-temperature fixing property of the toner, a proposal has been made to use a combination of an amorphous polyester resin that is incompatible with a crystalline polyester and a compatible polyester resin, in which the incompatible amorphous polyester ensures hot offset resistance, and the compatible amorphous polyester improves the low-temperature fixing property. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-116807 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, by using a compatible polyester resin with a medium softening point Tm to make the toner more compatible, the viscosity of the compatible polyester resin portion drops significantly when the toner becomes hot. This low-viscosity portion is unevenly distributed in the toner, which reduces the durability of the toner and causes it to stick to the magnetic roller during running, as well as reducing hot offset resistance during fixing. Specifically, in the toner of Patent Document 1, since the softening point Tm of the amorphous resin is low and the SP value is small, it is highly compatible with the crystalline polyester, and although the low-temperature fixing ability can be improved, the durability is insufficient. Also, when the softening point Tm of the resin composition C is between the softening points Tm of the amorphous resins A and B, the viscosity of the resin composition C is significantly reduced when it is compatible with the crystalline polyester, and the durability and hot offset resistance are significantly reduced.

[0006] Therefore, an object of the present invention is to provide a toner which is unlikely to cause burn-in over a long period of time and has excellent hot offset resistance and low-temperature fixing properties, and a two-component developer containing the toner. [Means for solving the problem]

[0007] The present inventors have conducted extensive research to solve the above problems, and as a result have found that a toner having toner particles containing a resin including amorphous resin A and amorphous resin B, each of which has a polyester as its main component and which has a specific SP value and melting temperature (softening point) Tm, hybrid resin C, which has a specific SP value and melting temperature Tm and which has a polyester moiety and a vinyl copolymer moiety, and crystalline resin D, each of which has a polyester as its main component, a colorant and a release agent, can provide a toner that is resistant to the burn-in phenomenon over a long period of time and has excellent hot offset resistance and low-temperature fixing properties, and have completed the present invention.

[0008] Thus, in accordance with the present invention, there is provided a toner having toner particles including a resin, a colorant, and a release agent, The resin includes an amorphous resin A mainly composed of a polyester, an amorphous resin B mainly composed of a polyester, and an amorphous resin C having a polyester moiety and a vinyl copolymer moiety, and a crystalline resin D mainly composed of a polyester, The amorphous resin A has a viscosity of 10.85 to 11.20 (cal / cm 3 ) 1 / 2 and a melting temperature Tm of 90 to 110°C, The amorphous resin B has a viscosity of 10.85 to 11.20 (cal / cm 3 ) 1 / 2 and a melting temperature Tm of 130 to 150°C, The hybrid resin C has a viscosity of 10.50 to 10.80 (cal / cm 3 ) 1 / 2 and a melting temperature Tm of 125 to 145°C. A toner is provided, which comprises:

[0009] According to the present invention, there is also provided a two-component developer comprising the above toner and a carrier. Effect of the Invention

[0010] According to the present invention, it is possible to provide a toner which is unlikely to cause burn-in over a long period of time and has excellent hot offset resistance and low-temperature fixing properties, and a two-component developer containing the toner.

[0011] The present inventors believe that the above-mentioned excellent effects are exhibited by the following mechanism. Amorphous resin (hereinafter also referred to as "resin C") made of hybrid resin C having polyester moieties and vinyl copolymer moieties has a characteristic of maintaining a high viscosity in a high temperature range compared to amorphous resin A (hereinafter also referred to as "resin A") mainly composed of polyester and amorphous resin B (hereinafter also referred to as "resin B") mainly composed of polyester. Therefore, by adding a hybrid body having a high melting temperature Tm, excessively low viscosity in a high temperature range can be suppressed, and high kneading strength can be maintained during melt kneading. In addition, since the SP value of resin C is closer to crystalline resin D (hereinafter also referred to as "resin D") mainly composed of polyester than resins A and B, resin D in the toner can be highly finely dispersed even when resins A and B, which are relatively incompatible, are used in combination. The more finely dispersed resin D is, the less it can be exposed to the toner surface, which improves durability, suppresses burning to the magnet roller during running, and improves hot offset resistance. Furthermore, by making the SP value of resin C closer to that of resin D than resins A and B, it is possible to create a state in which resin D is surrounded by resin C. This makes it possible to further reduce the exposure of resin D to the toner surface, and also improves low-temperature fixability because highly finely dispersed resin D quickly reduces the viscosity of the surrounding resins during heating for fixing. Even in the high fixing temperature range, resin C maintains a relatively high viscosity, and the relatively incompatible resins A and B are present in the toner in sufficient proportions, making it possible to suppress excessive viscosity reduction caused by resin D, thereby improving hot offset resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] (A) Toner The toner of the present invention is a toner having toner particles including a resin, a colorant, and a release agent, The resin includes an amorphous resin A mainly composed of a polyester, an amorphous resin B mainly composed of a polyester, and an amorphous resin C having a polyester moiety and a vinyl copolymer moiety, and a crystalline resin D mainly composed of a polyester, The amorphous resin A has a viscosity of 10.85 to 11.20 (cal / cm 3 ) 1 / 2 and a melting temperature Tm of 90 to 110°C, The amorphous resin B has a viscosity of 10.85 to 11.20 (cal / cm 3 ) 1 / 2 and a melting temperature Tm of 130 to 150°C, The hybrid resin C has a viscosity of 10.50 to 10.80 (cal / cm 3 ) 1 / 2 and a melting temperature Tm of 125 to 145°C. It is characterized by: The resin and the release agent, which are characteristic parts of the toner of the present invention, will be described below, followed by the toner and other basic components, and a two-component developer containing the toner.

[0013] (1) Resin The resin constituting the toner of the present invention is a combination of at least four resins having specific SP values ​​and melting temperatures Tm.

[0014] (1-1) Physical properties of amorphous resin A (resin A) Resin A is mainly composed of polyester and has a viscosity of 10.85 to 11.20 (cal / cm 3 ) 1 / 2 and a melting temperature Tm of 90 to 110°C. SP value is 10.85 (cal / cm 3 ) 1 / 2 If the SP value is less than 11.20 (cal / cm2), the resin becomes more compatible with resin D, and durability may decrease. 3 ) 1 / 2If the amount exceeds this range, the resin becomes less compatible with resin D, the kneading state during toner preparation deteriorates, and poor dispersion of resin D occurs, which may result in poor low-temperature fixability. The preferred SP value of resin A is 10.95 to 11.10 (cal / cm 3 ) 1 / 2 It is. If the melting temperature Tm is less than 90° C., the viscosity of the toner decreases, which may deteriorate the durability and hot offset resistance, whereas if the melting temperature Tm is more than 110° C., the viscosity of the toner increases, which may deteriorate the low-temperature fixability. The melting temperature Tm of the resin A is preferably 95 to 105°C.

[0015] (1-2) Physical properties of amorphous resin B (resin B) Resin B is mainly composed of polyester and has a viscosity of 10.85 to 11.20 (cal / cm 3 ) 1 / 2 and a melting temperature Tm of 130 to 150°C. SP value is 10.85 (cal / cm 3 ) 1 / 2 If the SP value is less than 11.20 (cal / cm2), the resin becomes more compatible with resin D, and durability may decrease. 3 ) 1 / 2 If the amount exceeds this range, the resin becomes less compatible with resin D, the kneading state during toner preparation deteriorates, and poor dispersion of resin D occurs, which may result in poor low-temperature fixability. The preferred SP value of resin B is 10.95 to 11.10 (cal / cm 3 ) 1 / 2 It is. If the melting temperature Tm is less than 130° C., the viscosity of the toner decreases, which may deteriorate the durability and hot offset resistance, whereas if the melting temperature Tm is more than 150° C., the viscosity of the toner increases, which may deteriorate the low-temperature fixability. The melting temperature Tm of the resin B is preferably 135 to 145°C.

[0016] (1-3) Physical properties of hybrid resin C (resin C) Resin C has a polyester moiety and a vinyl copolymer moiety, and has a viscosity of 10.50 to 10.80 (cal / cm 3 ) 1 / 2 and a melting temperature Tm of 125 to 145°C. SP value is 10.50 (cal / cm 3 ) 1 / 2 If the SP value is less than 10.80 (cal / cm2), the resin becomes more compatible with resin D, and durability may decrease. 3 ) 1 / 2 If the amount exceeds this range, the resin becomes less compatible with resin D, the kneading state during toner preparation deteriorates, and poor dispersion of resin D occurs, which may result in poor low-temperature fixability. The preferred SP value of resin C is 10.55 to 10.75 (cal / cm 3 ) 1 / 2 It is. Furthermore, if the melting temperature Tm is less than 125° C., the viscosity of the toner decreases, which may deteriorate the durability and hot offset resistance, whereas if the melting temperature Tm exceeds 145° C., the viscosity of the toner increases, which may deteriorate the low-temperature fixability. The melting temperature Tm of the resin C is preferably 130 to 140°C.

[0017] (1-4) Physical properties of crystalline resin D (resin D) Resin D is mainly composed of polyester. Resin D is 9.40 to 9.60 (cal / cm 3 ) 1 / 2 It is preferred that the SP value is 0.05 to 0.15. By setting the SP value of Resin D within the above range, the compatibility between Resins A to C and Resin D becomes more optimal, and the durability of the toner can be improved while maintaining high low-temperature fixability. SP value is 9.40 (cal / cm 3 ) 1 / 2 If the SP value is less than 9.60 (cal / cm), the compatibility with resins A to C is unlikely to deteriorate (it becomes easy to become compatible), so the kneading state deteriorates, and poor dispersion of resin D occurs, which may deteriorate the low-temperature fixability. 3 ) 1 / 2 If it exceeds this value, the resin may become easily miscible with the amorphous polyester, resulting in a decrease in durability. The more preferable SP value of resin D is 9.45 to 9.55 (cal / cm 3 ) 1 / 2 It is.

[0018] (1-5) Materials for Resins A, B and D Resins A, B, and D are polyester-based resins whose main component is polyester, with resins A and B being amorphous and resin D being crystalline. As long as they have the above-mentioned specific physical properties, any polyester-based resin commonly used in the relevant technical field can be used, and they can be prepared by polymerizing appropriate monomers, or commercially available products can be used. The polyester resin is usually obtained by subjecting one or more selected from a dihydric alcohol component and a trihydric or higher polyhydric alcohol component to a condensation polymerization reaction, esterification, or transesterification reaction by a known method with one or more selected from a divalent carboxylic acid and a trivalent or higher polycarboxylic acid. The conditions for the polycondensation reaction may be appropriately set depending on the reactivity of the monomer components, and the reaction may be terminated when the polymer has suitable physical properties. For example, the reaction temperature is about 170 to 250° C., and the reaction pressure is about 5 mmHg to normal pressure.

[0019] (1-5-1) Resins A and B (non-crystalline polyester resins) The amorphous polyester resin is not particularly limited, but can be obtained, for example, by a polycondensation reaction between a carboxylic acid monomer containing terephthalic acid or isophthalic acid as a main component and a polyhydric alcohol containing ethylene glycol as a main component. The reaction conditions are the same as those for producing ordinary polyester resins, and for example, a dicarboxylic acid monomer and a polyhydric alcohol are reacted in a nitrogen gas atmosphere, optionally in the presence of an esterification catalyst, at a temperature of 190 to 240° C. to obtain an amorphous polyester resin. The reaction ratio of the polyhydric alcohol and the carboxylic acid monomer is preferably 1.3:1 to 1:1.2 in terms of the equivalent ratio of hydroxyl group to carboxyl group [OH]:[COOH].

[0020] The molar content of terephthalic acid or isophthalic acid in the dicarboxylic acid monomer is preferably 70 to 100%, and more preferably 80 to 100%. The dicarboxylic acid monomer may also include aromatic dicarboxylic acids such as fumaric acid, aliphatic dicarboxylic acids such as adipic acid, sebacic acid, and succinic acid, and may also include ester-forming derivatives of terephthalic acid or isophthalic acid, ester-forming derivatives of aromatic dicarboxylic acids, ester-forming derivatives of aliphatic dicarboxylic acids, and acid anhydrides and alkyl esters of these carboxylic acids. Furthermore, the dicarboxylic acid monomer may be used in combination with a trivalent or higher polycarboxylic acid such as trimellitic acid or pyromellitic acid, or an ester-forming derivative thereof. The above dicarboxylic acid monomers and polycarboxylic acid monomers can be used alone or in combination of two or more.

[0021] The molar content of ethylene glycol in the polyhydric alcohol is preferably 70 to 100%, and more preferably 80 to 100%. The polyhydric alcohol may include other polyhydric alcohols such as 1,3-propylene glycol, 1,4-butanediol, and the like. The above polyhydric alcohols can be used alone or in combination of two or more.

[0022] (1-5-2) Resin D (crystalline polyester resin) The crystalline polyester resin is not particularly limited, but is preferably composed of a linear saturated aliphatic polyester unit obtained by a polycondensation reaction between a carboxylic acid monomer containing, as a main component, an aliphatic dicarboxylic acid having 9 to 22 carbon atoms and a polyhydric alcohol containing, as a main component, an aliphatic diol having 2 to 10 carbon atoms. The reaction conditions are the same as those for producing a normal polyester resin, and for example, a crystalline polyester resin is obtained by reacting a dicarboxylic acid monomer with a polyhydric alcohol in a nitrogen gas atmosphere, optionally in the presence of an esterification catalyst, at a temperature of 190 to 240° C. From the viewpoint of the storage stability of the toner, the reaction ratio of the polyhydric alcohol to the carboxylic acid monomer is preferably 0.83:1 to 1.3:1 in terms of the equivalent ratio of hydroxyl group to carboxyl group [OH]:[COOH].

[0023] The molar content of dicarboxylic acid in the carboxylic acid monomer is preferably 90 to 100%. If the molar content of dicarboxylic acid is low, the rate and speed of crystallization may decrease, resulting in insufficient toner aggregation resistance. Examples of the aliphatic dicarboxylic acid having 9 to 22 carbon atoms include azelaic acid, zebaic acid, 1,10-decanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc. The carboxylic acid monomer and polycarboxylic acid monomer may contain an ester-forming derivative of these aliphatic dicarboxylic acids. Furthermore, the carboxylic acid monomer may be used in combination with a polycarboxylic acid having three or more valences, such as trimellitic acid or pyromellitic acid, or an ester-forming derivative thereof. The above carboxylic acid monomers can be used alone or in combination of two or more.

[0024] The molar content of the aliphatic diol having 2 to 10 carbon atoms in the polyhydric alcohol is preferably 80 to 100%. Examples of the aliphatic diol having 2 to 10 carbon atoms include ethylene glycol, 1,4-butanediol, and 1,6-hexanediol. Furthermore, examples of polyhydric alcohols that can be used in combination with the above aliphatic diols include trihydric or higher alcohols such as glycerin and trimethylolpropane. The above polyhydric alcohols can be used alone or in combination of two or more.

[0025] (1-5-3) Amorphous resin and crystalline resin In the present invention, amorphous resins and crystalline resins are distinguished by their crystallinity index, with resins having a crystallinity index in the range of 0.6 to 1.5 being crystalline resins, and resins having a crystallinity index less than 0.6 or more than 1.5 being amorphous resins. That is, resins having a crystallinity index greater than 1.5 are amorphous, while resins having a crystallinity index less than 0.6 have low crystallinity and many amorphous portions. The crystallinity index is a physical property that is an index of the degree of crystallization of a resin, and is defined as the ratio of the softening temperature to the highest endothermic peak temperature (softening temperature / highest endothermic peak temperature). Here, the highest endothermic peak temperature refers to the temperature of the highest endothermic peak observed. In a crystalline polyester resin, the highest peak temperature is the melting point Tmp, and in a non-crystalline polyester resin, the highest endothermic peak is the glass transition temperature Tg. The degree of crystallization can be controlled by adjusting the types and ratio of raw material monomers, as well as production conditions (eg, reaction temperature, reaction time, cooling rate), and the like.

[0026] The mass average molecular weights of resins A, B and D have little effect on the effects of the present invention and are not particularly limited. Resin A is about 2,000 to 20,000, resin B is about 100,000 to 10,000,000, and resin D is about 3,000 to 50,000. Specific examples of resins A, B and D include resins A1 to A5, resins B1 to B5 and resins D1 to D5 produced in the examples.

[0027] (1-6) Materials for Resin C Resin C is an amorphous resin made of hybrid resin C having a polyester moiety and a vinyl copolymer moiety, in other words, a composite resin of a polyester resin and a vinyl resin. Resin C can be obtained, for example, by a method including a step of obtaining a polyester resin by polycondensing an alcohol component and a carboxylic acid component (referred to as "raw material monomer for amorphous polyester resin" in the examples) and a step of addition polymerizing a raw material monomer for a vinyl resin in the presence of a polymerization initiator such as dibutyl peroxide to obtain a vinyl resin. For example, the polycondensation reaction between an alcohol component containing a divalent or higher alcohol and a carboxylic acid component containing a divalent or higher carboxylic acid compound can be carried out in an inert gas atmosphere and, if necessary, in the presence of an esterification promoter such as gallic acid, a polymerization inhibitor, etc. This is a composite resin made of a polyester resin containing 3 to 18 moles of an aromatic carboxylic acid compound with a valence of 3 or more per 100 moles of an alcohol component, and a vinyl resin which is an addition polymer of raw material monomers containing 25 to 50 mass% or less of an alkyl (meth)acrylate ester.

[0028] Examples of the alcohol component include alkylene oxide adducts of bisphenol A, for example, a mixture of an ethylene oxide adduct of bisphenol A and a propylene oxide adduct of bisphenol A; diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, bisphenol A, and hydrogenated bisphenol A; and trihydric or higher alcohols such as sorbitol, pentaerythritol, glycerin, and trimethylolpropane.

[0029] The carboxylic acid component preferably contains a trivalent or higher aromatic carboxylic acid and a divalent carboxylic acid (dicarboxylic acid). Aromatic dicarboxylic acids include, for example, phthalic acid, isophthalic acid, terephthalic acid; the anhydrides of these acids; and the alkyl esters of these acids. Examples of aliphatic dicarboxylic acids include succinic acid, fumaric acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, dodecanoic diacid, tetradecanoic diacid, succinic acid having an alkyl or alkenyl group on the side chain, and anhydrides of these acids.

[0030] The raw material monomer for the vinyl resin preferably contains (meth)acrylic acid (represented as "ambireactive monomer" in the Examples), (meth)acrylic acid alkyl ester, and further styrene or a styrene derivative. Examples of (meth)acrylic acid alkyl esters [referred to as "raw material monomers for styrene-based resins" in the examples] include methyl (meth)acrylate, ethyl (meth)acrylate, (iso)propyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, and (iso- or tertiary)butyl (meth)acrylate. As used herein, "(meth)acrylic" means "methacrylic" or "acrylic". Styrene and styrene derivatives include, for example, styrene, α-methylstyrene, vinyltoluene and derivatives thereof. Examples of raw material monomers for other vinyl resins include ethylenically unsaturated monoolefins such as ethylene and propylene; diolefins such as butadiene; halovinyls such as vinyl chloride; vinyl esters such as vinyl acetate and vinyl propionate; ethylenic monocarboxylate esters such as dimethylaminoethyl (meth)acrylate; vinyl ethers such as vinyl methyl ether; vinylidene halides such as vinylidene chloride; and N-vinyl compounds such as N-vinylpyrrolidone.

[0031] Examples of resin C include the amorphous composite resin described in Japanese Patent No. 6675263 and the amorphous hybrid resin containing an amorphous condensation polymerization resin component and an addition polymerization resin component described in Japanese Patent Laid-Open No. 2013-109237. Specific examples include resins C1 to C5 produced in the examples. The mass average molecular weight of Resin C has little effect on the effects of the present invention and is not particularly limited, but is about 100,000 to 10,000,000.

[0032] (1-7) Resin Mixture Ratio The amount of the resin contained in the toner base particles may be appropriately determined so as to obtain the desired effects of the present invention. For example, the blending ratios of resin A, resin B, resin C and resin D in the toner base particles are 20 to 50% by mass, 20 to 60% by mass, 5 to 25% by mass and 1 to 15% by mass, respectively.

[0033] The mass ratio B / C of resin B to resin C is preferably 1.5 to 6.0. By setting the ratio of resin B to resin C within the above range, it is possible to further increase the dispersibility of resin D while preventing excessively low viscosity in the high temperature range, thereby improving the durability of the toner while maintaining high low-temperature fixing properties. When the mass ratio B / C is less than 1.5, the ratio of resin C increases and the portion that is compatible with resin D becomes relatively large, which may result in a decrease in durability at high temperatures and a decrease in hot offset resistance. On the other hand, when the mass ratio B / C exceeds 6.0, the ratio of resin C decreases and the portion that is compatible with resin D becomes relatively small, which may result in a slow toner melting speed during fixing and a decrease in low-temperature fixing ability. The mass ratio B / C is more preferably 2.0 to 4.5. For example, the total amount of resin B and resin C in the toner base particles is 1.0 to 2.4 relative to the mass of resin A (1).

[0034] The mass ratio C / D of resin C to resin D is preferably 1.0 to 5.0. By setting the amount of resin C, which is highly compatible with resin D, to be added within the above range, the dispersion state of resin D in the toner is improved and the plasticizing effect of resin D on the amorphous resin is maximized, thereby improving low-temperature fixing properties. If the mass ratio C / D is less than 1.0, the dispersibility of resin D may deteriorate, resulting in a decrease in toner durability and hot offset resistance. On the other hand, if the mass ratio C / D exceeds 5.0, the plasticizing effect of resin D on resin C may be weakened, resulting in a decrease in low-temperature fixability. The mass ratio C / D is more preferably 1.5 to 4.0. For example, the total amount of resin C and resin D in the toner base particles is 0.3 to 0.8 relative to the mass of resin A, which is 1.

[0035] (2) Release agent As the release agent contained in the toner of the present invention, any release agent commonly used in the art can be used. For example, petroleum-based waxes such as paraffin wax and microcrystalline wax and their derivatives; hydrocarbon-based synthetic waxes such as Fischer-Tropsch wax, polyolefin wax (polyethylene wax, polypropylene wax, etc.), low molecular weight polypropylene wax and polyolefin polymer wax (low molecular weight polyethylene wax, etc.) and their derivatives; vegetable waxes such as carnauba wax, rice wax, candelilla wax and their derivatives, and Japan wax; animal waxes such as beeswax and spermaceti; oil-based synthetic waxes such as fatty acid amides and phenol fatty acid esters; long-chain carboxylic acids and derivatives thereof; long-chain alcohols and derivatives thereof; silicone-based polymers; higher fatty acids, etc. The above derivatives include oxides, block copolymers of vinyl monomers and wax, and graft modified products of vinyl monomers and wax. In the present invention, the above-mentioned release agents can be used alone or in combination of two or more.

[0036] Among the above-mentioned release agents, the release agent is preferably an ester wax obtained from a long-chain carboxylic acid and an alcohol. Examples of the ester wax include the ester waxes described in Japanese Patent No. 4435434 and Japanese Patent No. 6545538, and specifically, the waxes used in the examples. By using an ester wax that is compatible with resin D as the release agent, the crystallinity of resin D and the ester wax after melt kneading is increased compared to when each is used alone, thereby improving the durability of the toner.

[0037] The ester wax is preferably a wax having an ester component with a linear molecular structure. By making the molecular structure of the ester-based wax linear, the crystallinity of the resin D and the ester-based wax, which also have a linear structure, is increased compared to when each is used alone, which makes it possible to suppress the viscosity of the toner from decreasing when not heated, thereby improving the durability of the toner.

[0038] The content of the release agent in the toner of the present invention is not particularly limited, but is preferably 1 to 10% by mass. If the content of the releasing agent is within the above range, it is possible to form an image having a high image density and excellent image quality without impairing various physical properties of the toner.

[0039] (3) Coloring agent As the colorant contained in the toner of the present invention, various types and colors of organic and inorganic pigments and dyes commonly used in the art can be used, for example, black, white, yellow, orange, red, purple, blue and green colorants.

[0040] Examples of black colorants include carbon black, copper oxide, manganese dioxide, aniline black, activated carbon, non-magnetic ferrite, magnetic ferrite, and magnetite. Examples of white colorants include zinc oxide, titanium oxide, antimony white, and zinc sulfide.

[0041] Examples of yellow colorants include yellow lead, zinc yellow, cadmium yellow, yellow iron oxide, mineral fast yellow, nickel titanium yellow, navel yellow, naphthol yellow S, Hansa Yellow G, Hansa Yellow 10G, benzidine yellow G, benzidine yellow GR, quinoline yellow lake, permanent yellow NCG, tartrazine lake, CI Pigment Yellow 12, CI Pigment Yellow 13, CI Pigment Yellow 14, CI Pigment Yellow 15, CI Pigment Yellow 17, CI Pigment Yellow 93, CI Pigment Yellow 94, and CI Pigment Yellow 138.

[0042] Examples of orange colorants include red yellow lead, molybdenum orange, permanent orange GTR, pyrazolone orange, Balkan orange, industren brilliant orange RK, benzidine orange G, industren brilliant orange GK, CI pigment orange 31, and CI pigment orange 43.

[0043] Examples of red colorants include red iron oxide, cadmium red, red lead, mercury sulfide, cadmium, permanent red 4R, lithol red, pyrazolone red, watching red, calcium salt, lake red C, lake red D, brilliant carmine 6B, eosin lake, rhodamine lake B, alizarin lake, brilliant carmine 3B, CI pigment red 2, CI pigment red 3, CI pigment red 5, CI pigment red 6, CI pigment red 7, CI pigment red 8, CI pigment red 9, CI pigment red 10, CI pigment red 11, CI pigment red 12, CI pigment red 13, CI pigment red 14, CI pigment red 15, CI pigment red 16, CI pigment red 17, CI pigment red 18, CI pigment red 19, CI pigment red 20, CI pigment red 21, CI pigment red 22, CI pigment red 23, CI pigment red 24, CI pigment red 25, CI pigment red 26, CI pigment red 27, CI pigment red 28, CI pigment red 29, CI pigment red 30, CI pigment red 31, CI pigment red 32, CI pigment red 33, CI pigment red 34, CI pigment red 35, CI pigment red 36, CI pigment red 37, CI pigment red 38, CI pigment red 39 ... Examples of pigment red include CI Pigment Red 7, CI Pigment Red 15, CI Pigment Red 16, CI Pigment Red 48:1, CI Pigment Red 53:1, CI Pigment Red 57:1, CI Pigment Red 122, CI Pigment Red 123, CI Pigment Red 139, CI Pigment Red 144, CI Pigment Red 149, CI Pigment Red 166, CI Pigment Red 177, CI Pigment Red 178, and CI Pigment Red 222.

[0044] Purple colorants include, for example, manganese violet, fast violet B, and methyl violet lake. Examples of blue colorants include Prussian blue, cobalt blue, alkali blue lake, Victoria blue lake, phthalocyanine blue, metal-free phthalocyanine blue, partially chlorinated phthalocyanine blue, fast sky blue, indanthrene blue BC, CI pigment blue 15, CI pigment blue 15:2, CI pigment blue 15:3, CI pigment blue 16, and CI pigment blue 60. Examples of green colorants include chrome green, chromium oxide, pigment green B, mica light green lake, final yellow green G, and CI pigment green 7.

[0045] In the toner of the present invention, the above colorants may be used alone or in combination of two kinds, and the combination may be of different colors or the same color. Two or more kinds of colorants may be used in the form of composite particles. The composite particles can be produced, for example, by adding an appropriate amount of water, a lower alcohol, etc. to two or more kinds of colorants, granulating the mixture with a general granulator such as a high-speed mill, and drying the mixture. Furthermore, in order to uniformly disperse the colorant in the resin, the colorant may be used in the form of a master batch. The composite particles and the master batch are mixed into the toner composition during dry mixing.

[0046] The content of the colorant in the toner of the present invention is not particularly limited, but is preferably 1 to 10% by mass. If the content of the colorant is within the above range, it is possible to form an image having a high image density and excellent image quality without impairing various physical properties of the toner.

[0047] (4) Charge control agent The toner base particles of the present invention may contain a charge control agent, but preferably do not contain a charge control agent in order to suppress an increase in the amount of charge. As the charge control agent, a charge control agent for negative charge control commonly used in the art can be used. Examples of charge control agents for controlling negative charges include oil-soluble dyes such as oil black and spiron black, metal-containing azo compounds, azo complex dyes, metal naphthenates, metal complexes and metal salts of salicylic acid and its derivatives (metals include chromium, zinc, zirconium, etc.), boron compounds, fatty acid soaps, long-chain alkyl carboxylates, and resin acid soaps. In the toner of the present invention, the above charge control agents can be used alone or in combination of two or more.

[0048] The content of the charge control agent in the toner of the present invention is not particularly limited, but is preferably 0.1 to 5% by mass. If the content of the charge control agent is within the above range, it is possible to form an image having a high image density and excellent image quality without impairing various physical properties of the toner.

[0049] (5) Toner particles The toner base particles contained in the toner of the present invention contain at least a resin, a colorant and a release agent, and may contain known additives as necessary within the range that does not impair the effects of the present invention. The toner of the present invention is used as a one-component developer further containing an external additive in the toner base particles, or as a two-component developer further containing an external additive and mixed with a carrier. The toner before the addition of the external additive is also called "toner base particles". External additives generally have the function of improving the transportability and chargeability of the toner, as well as the stirring property with the carrier when the toner is used as a two-component developer.

[0050] As the external additive, any external additive commonly used in the art can be used, such as silica, titanium oxide, etc., and preferably those that have been surface-treated (hydrophobized) with silicone resin, silane coupling agent, etc. The average primary particle size of the external additive is not particularly limited, but is preferably 1 to 200 nm. The amount of the external additive to be added is not particularly limited, but is preferably 1 to 10 parts by weight, and more preferably 2 to 5 parts by weight, relative to 100 parts by weight of the toner base particles.

[0051] (6) Toner manufacturing method The toner base particles used in the present invention can be produced by a known method using a known device commonly used in the technical field, for example, a mixing step of mixing a coarsely pulverized molten kneaded product containing at least a resin, a colorant, and a release agent with a filler, a fine pulverizing step of finely pulverizing the mixture obtained in the mixing step, a classification step of classifying the finely pulverized product obtained in the fine pulverizing step, and a spheronization treatment step of spheronizing the classified product obtained in the classification step with hot air. Dry methods are preferred in that they require fewer steps and less equipment cost than wet methods, and among them, the pulverization method is particularly preferred. The conditions in each step may be appropriately set depending on the target material and the desired physical properties.

[0052] For mixing, a known device commonly used in the technical field can be used, for example, a Henschel-type mixer such as Henschel Mixer (product name, manufactured by Mitsui Mining Co., Ltd. (now Nippon Coke and Engineering Co., Ltd.)), Super Mixer (product name, manufactured by Kawata Corporation), or Mechano Mill (product name, manufactured by Okada Seiko Co., Ltd.), an Ang Mill (product name, manufactured by Hosokawa Micron Corporation), Hybridization System (product name, manufactured by Nara Machinery Works, Ltd.), or Cosmo System (product name, manufactured by Kawasaki Heavy Industries, Ltd.), etc. The melt kneading may be performed using known devices commonly used in the technical field, such as general kneaders such as twin-screw extruders, triple rolls, and lab blast mills. Specifically, for example, single-screw or twin-screw extruders such as TEM-100B (trade name, manufactured by Toshiba Machine Co., Ltd.), PCM-65 / 87, and PCM-30 (all of which are trade names, manufactured by Ikegai Corporation), and open-roll type kneaders such as Kneadex (trade name, manufactured by Mitsui Mining Co., Ltd.) may be used. For the fine pulverization, a known device commonly used in the art, such as a jet pulverizer that uses a supersonic jet stream to pulverize the material, or an impact pulverizer that introduces a solidified material into the space formed between a rotor and a stator (liner) rotating at high speed, can be used. For classification, a known device commonly used in the art, for example, a classifier capable of removing over-pulverized toner particles by centrifugal force and wind force, such as a swirling wind classifier (rotary wind classifier), can be used.

[0053] The toner of the present invention can be produced by a known method using a known device commonly used in the art, through a first external addition step of externally adding external silica to toner base particles, and a second external addition step of externally adding external fine particles. The conditions in each step may be appropriately set depending on the target material and the desired physical properties.

[0054] (B) Two-component developer The two-component developer of the present invention contains the toner of the present invention and a carrier. The toner of the present invention can be used in the form of either a one-component developer or a two-component developer. When used as a two-component developer, a carrier is further blended in addition to the external additive. As the carrier, any carrier commonly used in the art can be used, and examples thereof include single or composite ferrites made of iron, copper, zinc, nickel, cobalt, manganese, chromium, etc., and carrier core particles surface-coated with known coating materials. The average particle size of the carrier is preferably from 10 to 100 μm, and more preferably from 20 to 50 μm. The blending amounts of the toner and carrier are not particularly limited, but the content of the externally added toner in the two-component developer is preferably 3 to 12% by mass. EXAMPLES

[0055] The present invention will be specifically described below with reference to Production Examples, Examples and Comparative Examples, but the present invention is not limited to the following Examples as long as it does not depart from the gist of the present invention. In the examples and comparative examples, the physical properties were measured by the methods described below.

[0056] [Resin solubility parameter SP value: (cal / cm 3 ) 1 / 2 ] The solubility parameter SP value of the resin ((cal / cm)) was calculated by the method proposed by Fedors et al. in "POLYMER ENGINEERING AND SCIENCE" by Robert F. Fedors, Vol. 14, No. 2, pp. 147-154, February 1994. 3 ) 1 / 2 ) is calculated.

[0057] [Resin melting temperature Tm:℃] Using a flow characteristic evaluation device (Flow Tester, Shimadzu Corporation, Model: CFT-100C), 1 g of resin sample was heated at a temperature increase rate of 6°C / min while applying a load of 20 kgf / cm 2 (9.8×10 5 A pressure of 1 Pa is applied to the sample, and the sample is allowed to flow out from a die (nozzle diameter 1 mm, length 1 mm). The temperature at which half of the sample has flowed out is taken as the melting temperature Tm (℃) of the resin.

[0058] [Volume average particle size of toner particles: μm] 20 mg of sample and 1 ml of sodium alkyl ether sulfate are added to 50 ml of electrolyte (Beckman Coulter, Inc., product name: ISOTON-II), and the mixture is dispersed for 3 minutes at a frequency of 20 kHz using an ultrasonic disperser (As One Corporation, tabletop dual-frequency ultrasonic cleaner, model: VS-D100) to obtain a measurement sample. The obtained measurement sample is measured using a particle size distribution measuring device (Beckman Coulter, Inc., model: Multisizer4e) under the conditions of aperture diameter: 100 μm, measurement particle number: 50,000 counts, and the volume average particle size (μm) is calculated from the volume particle size distribution of the sample particles.

[0059] (Production Examples 1 to 5 and Comparative Production Examples 1 to 4: Preparation of Amorphous Polyester A) 100 parts by mass of raw material monomers of polyester resins with the molar ratio shown in Table 1, 0.5 parts by mass of tin (II) 2-ethylhexanoate as an esterification catalyst, and 0.05 parts by mass of gallic acid (3,4,5-trihydroxybenzoic acid) as an esterification promoter were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a downflow condenser, and a nitrogen inlet tube, and the temperature was raised to 210°C in a mantle heater in a nitrogen atmosphere over 5 hours. Then, the reaction was continued at a pressure of 8.0 kPa until the melting temperature Tm shown in Table 1 was reached, to obtain amorphous polyester resins A1 to A9. The melting temperature of the resulting resin was measured, and the obtained physical property values ​​are shown in Table 1 together with the resin raw materials and their usage ratios.

[0060] (Production Examples 6 to 10 and Comparative Production Examples 5 to 8: Preparation of Amorphous Polyester B) 100 parts by mass of raw material monomers of amorphous polyester resin other than trimellitic anhydride in the molar ratio shown in Table 2, 0.5 parts by mass of tin (II) 2-ethylhexanoate as an esterification catalyst, and 0.05 parts by mass of gallic acid as an esterification promoter were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a downflow condenser, and a nitrogen inlet tube, and the temperature was raised to 235 ° C. in a mantle heater in a nitrogen atmosphere over 3 hours, and after reaching a temperature of 235 ° C., the temperature was maintained for 7 hours. After that, the temperature was cooled to 210 ° C., trimellitic anhydride was added, the temperature was maintained at 210 ° C. for 1 hour, and a reduced pressure reaction was performed at a pressure of 8.0 kPa, and the reaction was continued until the melting temperature Tm shown in Table 2 was reached, and amorphous polyester resins B1 to B9 were obtained. The melting temperature of the resulting resin was measured, and the obtained physical property values ​​are shown in Table 2 together with the resin raw materials and their usage ratios.

[0061] (Production Examples 11 to 15 and Comparative Production Examples 9 to 12: Preparation of Hybrid Resin C) The raw material monomers of polyester resins other than trimellitic anhydride in the molar ratio shown in Table 3 were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a downflow condenser, and a nitrogen inlet tube, and the temperature was raised to 160°C in a mantle heater in a nitrogen atmosphere. A mixture of raw material monomers of styrene resins, bireactive monomers, and dibutyl peroxide as a polymerization initiator was dropped therein to perform polymerization. Then, 0.5 parts by mass of tin (II) 2-ethylhexanoate as an esterification catalyst and 0.05 parts by mass of gallic acid as an esterification promoter were added to 100 parts by mass of the monomers, and the temperature was raised to 210°C over 5 hours. Then, trimellitic anhydride was added, the temperature was raised to 220°C, and the reaction was carried out at a pressure of 8.0 kPa until the melting temperature Tm shown in Table 3 was reached, to obtain hybrid resins C1 to C9. The melting temperature of the resulting resin was measured, and the obtained physical property values ​​are shown in Table 3 together with the resin raw materials and their usage ratios.

[0062] (Production Examples 16 to 20: Preparation of Crystalline Polyester Resin D) 100 parts by mass of monomer components having the molar ratios shown in Table 4 and 0.2 parts by mass of tin(II) 2-ethylhexanoate as an esterification catalyst were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, and the temperature was raised from 130°C to 200°C over 10 hours under a nitrogen atmosphere. The mixture was then reacted at 200°C and a pressure of 8.0 kPa for 1 hour to obtain crystalline polyester resins D1 to D5. The solubility parameter SP of the obtained resin is shown in Table 4 together with the resin raw materials and their usage ratios.

[0063] [Table 1]

[0064] [Table 2]

[0065] [Table 3]

[0066] [Table 4]

[0067] (Production Example 21: Preparation of release agent W1) In a 2-liter four-neck flask equipped with a stirrer, a thermocouple, and a nitrogen inlet tube, 1.5 moles of stearic acid as an acid component and 1.5 moles of stearyl alcohol as an alcohol component were placed. An esterification reaction was carried out at 220°C under a nitrogen stream to obtain a reaction product. Then, 26 parts by mass of a mixed solvent of toluene and ethanol (mixed mass ratio 20:6) was added to the flask relative to 100 parts by mass of the esterification reaction product to dissolve the resulting reaction product. Furthermore, 10 parts by mass of a 10% by mass aqueous sodium hydroxide solution was added to the flask and stirred at a temperature of 70° C. for 30 minutes. The flask was left to stand for 30 minutes, and the contents of the flask were separated into an organic layer and an aqueous layer, and the aqueous layer was removed from the contents. Thereafter, 20 parts by mass of ion-exchanged water was added to the flask and stirred at a temperature of 70° C. for 30 minutes, and then the flask was left to stand for 30 minutes to separate the contents in the flask into an aqueous layer and an organic layer, and the aqueous layer was removed from the contents, and this operation was repeated five times. The solvent was distilled off from the organic layer of the contents in the flask under reduced pressure conditions to obtain an ester wax W1 having a linear structure.

[0068] (Production Example 22: Preparation of release agent W2) Instead of preparing wax, a commercially available linear paraffin wax (manufactured by Nippon Seiro Co., Ltd., product name: HNP-10PD, W2) was used.

[0069] (Production Example 23: Preparation of release agent W3) A three-dimensional structured ester wax W3 was obtained in accordance with Production Example 21 using 3 mol of stearic acid as the acid component and 0.75 mol of pentaerythritol as the alcohol component.

[0070] Example 1: Preparation of Toner [Material mixing, kneading, crushing, and classification processes] The toner base particles used in the examples and comparative examples were prepared as follows. Amorphous resin A: Resin A-1 (Production example 1) 30% by mass Amorphous resin B: Resin B-1 (Production Example 6) 40% by mass Amorphous resin consisting of hybrid resin C: Resin C-1 (Production Example 11) 14% by mass Crystalline resin D: Resin D-1 (Production Example 16) 8% by mass Colorant: Colorant (CI Pigment Blue 15:3, manufactured by DIC Corporation) 4% by mass Release agent: Wax W1 (Production Example 21) 3% by mass Charge control agent: Salicylic acid compound (Orient Chemical Industry Co., Ltd., product name: Bontro E84) 1% by mass

[0071] The above materials were premixed and dispersed for 5 minutes using an air flow mixer (Henschel mixer, manufactured by Mitsui Mining Co., Ltd. (now Nippon Coke and Engineering Co., Ltd.), model: FM20C), and then melt-kneaded using a twin-screw extruder (manufactured by Ikegai Corporation, model: PCM-30) under conditions of a cylinder setting temperature of 110°C, a barrel rotation speed of 300 rpm, and a raw material supply rate of 20 kg / hour to obtain a kneaded product. The resulting kneaded product was cooled with a cooling belt and then coarsely pulverized using a cutting mill (manufactured by Dalton, model: D-200) to obtain a coarsely pulverized product. The resulting coarsely crushed material was finely crushed in a jet mill (manufactured by Nippon Pneumatic Mfg. Co., Ltd., model: IDS-2) to obtain a finely crushed product. The resulting finely pulverized product was classified using an elbow jet classifier (manufactured by Nittetsu Mining Co., Ltd., model: EJ-LABO) to obtain toner base particles to which no external additives had been added.

[0072] [External addition process] To 100 parts by mass of the obtained toner base particles, 1.0 part by mass of a first external additive (hydrophobic fumed silica, average primary particle diameter 12 nm, manufactured by Aerosil, product name: R974) and 1.5 parts by mass of a second external additive (colloidal silica, average primary particle diameter 115 nm, manufactured by Cabot, product name: TG-C191) were added as external additives, and the mixture was stirred with the above-mentioned air flow mixer to obtain externally added toner base particles with a volume average particle diameter of 6.5 μm.

[0073] [Preparation of developer] The obtained externally added toner base particles and a coated carrier (manufactured by Sharp Corporation, name: genuine carrier for MX-5111FN) were put into a V-type mixer (manufactured by Tokuju Kogyosho Co., Ltd., product name: V-5) so that the toner concentration was 7% by mass, and mixed for 20 minutes to obtain a two-component developer.

[0074] (Examples 2 to 27 and Comparative Examples 1 to 12: Preparation of Toner) A toner and a two-component developer were obtained and evaluated in the same manner as in Example 1, except that resins A to D and release agents W1 to W3 in the blending ratios shown in Tables 5 and 6 were used.

[0075] <Evaluation> The additive toners and two-component developers prepared in Examples 1 to 27 and Comparative Examples 1 to 22 were evaluated for the following items, and a comprehensive evaluation was made based on the results.

[0076] <Magnet roller seizure evaluation> The external toner and two-component developer are filled into the developing device and toner cartridge of a commercially available color multifunction printer (manufactured by Sharp Corporation, model: BP-20C25). Next, a continuous print test of 50,000 sheets of A4 paper is performed in an environment of a temperature of 30°C and humidity of 80%, so that a square solid image (ID = 1.45 to 1.50) with a side length of 10 mm is formed at three points in the center and both ends of the axial direction of the developing roller. At that time, the image density at the beginning and after 50,000 sheets is measured using a colorimetric color difference meter (spectrodensitometer, manufactured by X-Rite, model: 504), and the image density difference (ΔID) between the beginning and after 50,000 sheets is measured.

[0077] From the results obtained, the image sticking phenomenon is evaluated according to the following criteria. ◎ (Excellent): No density loss (ΔID is less than 0.1) and No toner fusion on the developing roller surface ○ (Good): No decrease in density (ΔID is less than 0.1) and Toner fusion is observed on the developing roller surface. △ (Fair): There is a slight decrease in concentration (ΔID is 0.1 or more and less than 0.2) and Toner fusion is observed on the developing roller surface. × (Not acceptable): The concentration decrease is large (ΔID: 0.2 or more) and Toner fusion is observed on the developing roller surface.

[0078] <Fixation> A fixed image is produced using a two-component developer using a commercially available copying machine (Model: MX-6171, manufactured by Sharp Corporation) modified for the evaluation purpose. First, a sample image including a solid image area (a rectangle measuring 20 mm in length and 50 mm in width) was printed on recording paper (PPC paper, model: SF-4AM3, manufactured by Sharp Corporation) with the toner adhesion amount to the recording paper in the solid image area being 0.5 mg / cm 2 The toner image is adjusted so as to be an unfixed image. Next, a fixed image is produced using a belt fixing device. The fixing process speed is set to 200 mm / sec, the temperature of the fixing belt is increased in increments of 5° C. from 130° C., and the gloss and fixability are measured at each fixing temperature. Fixability is evaluated by determining a temperature range in which neither low-temperature offset nor high-temperature offset occurs, and the upper limit of that temperature range is defined as the "maximum fixing temperature" and the lower limit as the "minimum fixing temperature." The terms "high temperature offset" and "low temperature offset" are defined as a state in which toner is not fixed to the recording paper during fixing, but remains attached to the fixing belt and adheres to the recording paper after the fixing belt has made one revolution.

[0079] From the obtained results, the maximum fixing temperature is evaluated according to the following criteria. ◎ (Very good): Maximum fixing temperature is 200℃ or higher ○ (Good): The upper limit of the fixing temperature is 190°C or higher and less than 200°C. △ (slightly poor): The upper fixing temperature limit is between 180°C and 190°C. × (Fail): The upper limit of the fixing temperature is less than 180°C.

[0080] From the obtained results, the minimum fixing temperature is evaluated according to the following criteria. ◎ (Very good): Minimum fixing temperature is less than 130℃ ○ (Good): The minimum fixing temperature is 130°C or higher and less than 140°C. △ (slightly poor): The minimum fixing temperature is 140°C or higher and less than 150°C. × (bad): The minimum fixing temperature is 150°C or higher

[0081] <Overall rating> Based on the above evaluation results, an overall judgment was made according to the following criteria. ◎(Excellent): All evaluation items are ◎ (usable) ○ (Good): At least one evaluation item has a ○ (usable) △(OK): At least one evaluation item is △ (usable) × (Not available): There is an × in at least one evaluation item (not available)

[0082] Tables 5 and 6 show the physical properties and blending ratios of the resins and release agents constituting the toners of the Examples and Comparative Examples, and Table 7 shows the evaluation results of the toners and developers of the Examples and Comparative Examples. The items and abbreviations in Tables 5 and 6 have the following meanings: Materials: A1~A9, B1~B9, C1~C9, D1~D9 for each resin, W1~W3 for each wax SP: Solubility parameter of resin ((cal / cm 3 ) 1 / 2 ) Tm: Melting temperature of resin (℃) Proportion: mass proportion in toner base particles (mass%) The total of resins A to D is 92% by mass, and the rest are additive components. Material ratio: Mass ratio of resin B to C, resin C to D Type: Release agent type (E: ester wax, P: paraffin wax) Structure: Molecular structure of release agent (SC: linear structure, SS: three-dimensional structure)

[0083] [Table 5]

[0084] [Table 6]

[0085] [Table 7]

[0086] The results in Table 1 reveal the following: (1) The toner of the present invention, although there are various advantages and disadvantages, is unlikely to cause burn-in phenomenon over a long period of time and has excellent hot offset resistance and low-temperature fixing properties, and a two-component developer containing the toner can be provided (Examples 1 to 27). (2) The toner of the present invention has an SP value of resin A of 10.85 to 11.20 (cal / cm 3 ) 1 / 2 (See Examples 1, 2-3, and Comparative Examples 1-2) (3) The toner of the present invention exhibits excellent effects when the melting temperature Tm of the resin A is in the range of 90 to 110° C. (see Examples 1, 4 to 5, and Comparative Examples 3 to 4). (4) The toner of the present invention has an SP value of resin B of 10.85 to 11.20 (cal / cm 3 ) 1 / 2 (See Examples 1, 6-7, and Comparative Examples 5-6) (5) The toner of the present invention exhibits excellent effects when the melting temperature Tm of the resin B is in the range of 130 to 150° C. (see Examples 1, 8 to 9, and Comparative Examples 7 to 8). (6) In the toner of the present invention, the SP value of the resin C is 10.50 to 10.80 (cal / cm 3 )1 / 2 (See Examples 1, 10-11, and Comparative Examples 9-10) (7) The toner of the present invention exhibits excellent effects when the melting temperature Tm of the resin C is in the range of 125 to 145° C. (see Examples 1, 12 to 13, and Comparative Examples 11 to 12). (8) In the toner of the present invention, the SP value of the resin D is 9.40 to 9.60 (cal / cm 3 ) 1 / 2 (See Examples 1 and 14 to 17.) (9) The toner of the present invention exhibits excellent effects when the mass ratio B / C of resin B to resin C is in the range of 1.5 to 6.0 (see Examples 1, 18 to 19, and 22 to 23). (10) The toner of the present invention exhibits excellent effects when the mass ratio C / D of resin C to resin D is in the range of 1.0 to 5.0 (see Examples 1, 20 to 21, and 24 to 25). (11) The toner of the present invention exhibits excellent effects when the release agent is an ester wax (see Examples 1 and 26). (12) The toner of the present invention exhibits excellent effects when the release agent contains an ester component having a linear molecular structure (see Examples 1 and 27).

Claims

1. a toner having toner particles including a resin, a colorant, and a release agent; The resin includes an amorphous resin A mainly composed of a polyester, an amorphous resin B mainly composed of a polyester, and an amorphous resin C having a polyester moiety and a vinyl copolymer moiety, and a crystalline resin D mainly composed of a polyester, The amorphous resin A has a viscosity of 10.85 to 11.20 (cal / cm 3 ) 1 / 2 and a melting temperature Tm of 90 to 110°C, The amorphous resin B has a viscosity of 10.85 to 11.20 (cal / cm 3 ) 1 / 2 and a melting temperature Tm of 130 to 150° C., The hybrid resin C has a viscosity of 10.50 to 10.80 (cal / cm 3 ) 1 / 2 and a melting temperature Tm of 125 to 145°C, The crystalline resin D has an SP value of 9.40 to 9.60 (cal / cm 3 ) 1 / 2 . A toner characterized by:

2. 2. The toner according to claim 1, wherein a mass ratio B / C of the amorphous resin B to the amorphous resin C is 1.5 to 6.

0.

3. 3. The toner according to claim 1, wherein a mass ratio C / D of the hybrid resin C to the crystalline resin D is 1.0 to 5.

0.

4. 4. The toner according to claim 1, wherein the releasing agent is an ester wax.

5. 5. The toner according to claim 4, wherein the ester wax is a wax having an ester component with a linear molecular structure.

6. 6. A two-component developer comprising the toner according to claim 1 and a carrier.

Citation Information

Patent Citations

  • Toner and production method of toner

    JP2012155103A

  • Toner for electrostatic charge development, image forming apparatus using the same, and image forming method

    JP2013167702A

  • Toner, image forming apparatus, image forming method, and process cartridge

    JP2014074882A

  • Developer for electrostatic latent image development, and image forming apparatus

    JP2014170103A

  • Binder resin composition for toner

    JP2017090889A